Cohesion in Oedipus the King by Sophocles: A Discourse Analysis - Hanni Nurliani (Passage, 2017)
Cohesion in a literary text appears to receive less scholarly attention, and the present study attempts to explore how cohesion is realized in a dramatic text Oedipus the King. This study, therefore, examines the use of grammatical and lexical cohesive devices in the dramatic text and its contribution to how the story proceeds. This study is descriptive in nature. In analyzing the data, this study employs theoretical frameworks based on Halliday and Hasan (1976) concerning the concept of cohesive device analysis and Gerot‟s and Wignell‟s point of view (1994) on cohesion interpretation. The data include the expressions used in the drama, and the analysis focuses on the realization of cohesive devices in the text. This study reveals that the text applies all types of cohesive devices, which cover 1,606 grammatical cohesive devices and 341 lexical cohesive devices. This study also shows six ways in which cohesive devices contribute to how the story proceeds. They are (1) to keep track of the participants, (2) to avoid repetition and text redundancy, (3) to control the discourse direction, (4) to emphasize an event, (5) to reduce monotony in language use, and (6) to add information on participants or events. This study is expected to contribute to the understanding of how a story is presented in a literary work, especially a dramatic text.Keywords: grammatical cohesive device, lexical cohesive device, dramatic text, discourse analysis